SISTEM INFORMASI PERSEDIAAN BARANG PADA PT. SURYA NUSA BHAKTINDO BENGKULU - Yulianti, Liza; Yupianti, Yupianti (UNIVED Press, 2012)
One effort to present information about the construction material supply house, is one of them by making Materials Inventory application using Microsoft Visual Basic 6.0. This is a software program (software) that is used in the design of a program. In addition, Microsoft Visual Basic 6 is also equipped with a more complete capabilities, are easy to use in the design of a program, coupled with connections that support a variety of databases. Goals to be achieved in this research is to make the Inventory Application at PT. Solar Nusa Bhaktindo Bengkulu so it can be used as a media support in making information to the leadership. This information system will display the transaction information materials based on income and expenses